A prospective cluster randomized trial of an interventions bundle to reduce inappropriate antibiotic use for upper respiratory tract infections in the outpatient setting - Adeel A. Butt; Sherin Shams; Atika Jabeen; Asma Ali Al-Nuaimi; Jeyaram Illiayaraja Krishnan; Aimon B. Malik; Samah Saleem; Maryam Hassan Abdulaziz; Naheel Ismail Seyam; Kamran Aziz; Dalia Kandil; Anil G. Thomas; et al. (BMC Infectious Diseases)
Abstract Background Antibiotic overuse and increasing antimicrobial resistance are global public health threats. We determined the impact of a multicomponent intervention in reducing inappropriate antibiotic use for upper respiratory tract infections (URTIs) in the outpatient setting. Methods Design Prospective, cluster-randomized trial. Intervention Bundled 4-component intervention including extensive provider education, a decision support algorithm, option for deferred antibiotics prescription, and monthly feedback on prescription patterns, vs. a single randomly assigned intervention (decision support algorithm). Setting Four Primary healthcare centers in Qatar with study period from August 2023 to October 2024. Participants Individuals with a diagnosis of URTI who were prescribed antibiotics. Main outcome(s) Reduction in inappropriate antibiotic prescriptions for URTIs in the intervention vs. control group during the 11-month follow-up period. Results We analyzed 20,062 episodes-of-care for URTIs with an antibiotic prescription (9,277 at control and 10,785 at intervention sites). In a mixed effects logistic regression model accounting for the clustering effect, the intervention was associated with a 29% reduction in odds of inappropriate antibiotics prescriptions ( [aOR] 0.71; 95% CI 0.66–0.77). The relative reduction was 20.9% (44.9% vs. 35.5%; p < 0.001) between the two groups. The relative drop in inappropriate antibiotic prescriptions before and after the interventions was 16.3% (42.4% vs 35.5%; p < 0.001) at intervention sites (p < 0.001) compared with 2.2% (45.9% to 44.9%; p = 0.4) at control sites. Senior-most physicians and younger population (19–40 years old) were more likely to prescribe or receive inappropriate antibiotic prescription. Conclusion A multi-component intervention can significantly reduce inappropriate antibiotic prescriptions for URTIs in the outpatient setting. ClinicalTrials.gov ID NCT06135376, Registration Date: November 9, 2023.